(untitled) - Speight, James G. (New Jersey, 2005)
All the guidance needed to test coal and analyze the results. With the skyrocketing costs of most fuel sources, government, industry, and consumers are taking a greater interest in coal, an abundant and inexpensive alternative, which has been made more environmentally friendly through new technology. Published in response to this renewed interest, Handbook of Coal Analysis provides readers with everything they need to know about testing and analyzing coal. Moreover, it explains the meaning of test results and how these results can predict coal behavior and its corresponding environmental impact during use.
Keywords: Coal; Analysis,Handbook, manuals, etc